A Perfect Storm: Increased Colonization and Failure of Vaccination Leads to Severe Secondary Bacterial Infection in Influenza Virus-Infected Obese Mice - Erik A. Karlsson (American Society for Microbiology, 2017)
ABSTRACT Obesity is a risk factor for developing severe disease following influenza virus infection; however, the comorbidity of obesity and secondary bacterial infection, a serious complication of influenza virus infections, is unknown. To fill this gap in knowledge, lean and obese C57BL/6 mice were infected with a nonlethal dose of influenza virus followed by a nonlethal dose of Streptococcus pneumoniae. Strikingly, not only did significantly enhanced death occur in obese coinfected mice compared to lean controls, but also high mortality was seen irrespective of influenza virus strain, bacterial strain, or timing of coinfection. This result was unexpected, given that most influenza virus strains, especially seasonal human A and B viruses, are nonlethal in this model. Both viral and bacterial titers were increased in the upper respiratory tract and lungs of obese animals as early as days 1 and 2 post-bacterial infection, leading to a significant decrease in lung function. This increased bacterial load correlated with extensive cellular damage and upregulation of platelet-activating factor receptor, a host receptor central to pneumococcal invasion. Importantly, while vaccination of obese mice against either influenza virus or pneumococcus failed to confer protection, antibiotic treatment was able to resolve secondary bacterial infection-associated mortality. Overall, secondary bacterial pneumonia could be a widespread, unaddressed public health problem in an increasingly obese population. IMPORTANCE Worldwide obesity rates have continued to increase. Obesity is associated with increased severity of influenza virus infection; however, very little is known about respiratory coinfections in this expanding, high-risk population. Our studies utilized a coinfection model to show that obesity increases mortality from secondary bacterial infection following influenza virus challenge through a “perfect storm” of host factors that lead to excessive viral and bacterial outgrowth. In addition, we found that vaccination of obese mice against either virus or bacteria failed to confer protection against coinfection, but antibiotic treatment did alleviate mortality. Combined, these results represent an understudied and imminent public health concern in a weighty portion of the global population.